Phenylboronic acid-catalyzed tandem construction of S-S and C-S bonds: a new method for the synthesis of benzyl disulfanylsulfone derivatives from S-benzyl thiosulfonates - Reddy, Raju Jannapu; Waheed, Md; Krishna, Gamidi Rama (Organic & Biomolecular Chemistry, 2020)
A unique phenylboronic acid-catalyzed dimerization-sulfonylation of S-benzyl thiosulfonates has been disclosed. A metal-free tandem construction of S-S and C-S bonds is an operationally simple method to access a wide range of benzyl disulfanylsulfone derivatives in high to excellent yields. Moreover, the robustness of this tandem transformation has been demonstrated by gram-scale reactions, and a plausible mechanism is also proposed.